Pre-procedural abnormal von Willebrand factor function predicts clinical outcomes after Transcatheter Aortic Valve Implantation: a prospective cohort study - Abu Khadija, Haitham; Alnees, Mohammad; Ayyad, Omar; Gandelman, Gera; Abu Hamdeh, Nizar; Haim, Amir; Hamdan, Yazan; Cohen, Ramon; Najajra, Duha; Kirzhner, Alena; Schiller, Tal; George, Jacob; et al. (Frontiers in Cardiovascular Medicine, 2025)
Background and objectivesTranscatheter Aortic Valve Implantation (TAVI) is a minimally invasive intervention for aortic stenosis, which is associated with the potential for major vascular complications and arrhythmias. This study aims to identify primary predictors of these complications, emphasizing the roles of Decreased Platelet Count (DPC) and Acquired Von Willebrand Syndrome (AVWS).MethodsWe performed a prospective study with 80 patients planning to receive TAVI at the Heart Center, Kaplan Medical Center, Rehovot, Israel. Pre-procedural evaluations include the measurement of baseline platelet counts and the functionality of the von Willebrand factor. The DPC was determined as the percentage decreased from baseline to the lowest count. AVWS was diagnosed through the assessment of von Willebrand factor activity and antigen concentrations.ResultsOur results demonstrate that both DPC and AVWS are crucial predictors of major vascular complications. Specifically, patients with a DPC exceeding 20% exhibited a coefficient (Coef) of 1.276 (p = 0.072; 95% CI: −0.116 to 2.668) for complications. While, patients with abnormal von Willebrand factor function presented an Coef of 1.841 (p = 0.022; 95% CI: 0.271–3.410) for complications compared to those without AVWS. ROC curve analysis indicated an AUC of 0.7417 for the DPC model and 0.8025 for the AVWS model in predicting major vascular complications. In the arrhythmia model, AVWS appeared as a significant predictor of arrhythmias, with an OR of 4.480 [95% CI: (1.21, 16.49), p = 0.024].ConclusionsAssessing both DPC and von Willebrand factor function is crucial for predicting post-TAVI complications.